Noradrenaline Acting on Alpha1 Adrenoceptor as well as by Chelating Iron Reduces Oxidative Burden on the Brain: Implications With Rapid Eye Movement Sleep - Singh, Abhishek; Das, Gitanjali; Kaur, Manjeet; Mallick, Birendra N. (Frontiers in Molecular Neuroscience, 2019)
Noradrenaline (NA) level in the brain is reduced during rapid eye movement sleep (REMS). However, upon REMS deprivation (REMSD) its level is elevated, which induces apoptosis and degeneration of neurons in the brain. In contrast, isolated studies have reported that NA possesses anti-oxidant property, while REMSD reduces lipid peroxidation (LP) and reactive oxygen species (ROS). We argued that an optimum level of NA is likely to play physiologically beneficial role. To resolve the contradiction and for better understanding of the role of NA in the brain, we estimated LP and ROS levels in synaptosomes prepared from the brains of control and REMS deprived rats with or without in vivo treatment with either α1-adrenoceptor (AR) antagonist, prazosin (PRZ) or α2-AR agonist, clonidine (CLN). REMSD significantly reduced LP and ROS in synaptosomes; while the effect on LP was ameliorated by both PRZ and CLN, ROS was prevented by CLN only. Thereafter, we evaluated in vitro the effects of NA, Vit E, Vit C and Desferrioxamine (DFX, iron chelator) in modulating hydrogen peroxide (H2O2)-induced LP and ROS in rat brain synaptosomes, Neuro2a and C6 cells. We observed that NA prevented ROS generation by chelating iron (inhibiting Fenton reaction). Also, interestingly lower dose of NA protected, while at higher dose it damaged the neurons and glia. These in vitro and in vivo results are complementary and support our contention. Based on the findings we propose that REMS maintains optimum level of NA in the brain (an antioxidant compromised organ) to protect the latter from continuous oxidative onslaught.